No Evidence of Infectious Retroviruses in Measles Virus Vaccines Produced in Chicken Embryo Cell Cultures - Shahabuddin, Muhammad (American Society for Microbiology, 2001)
All vaccines that are prepared in chicken embryo fibroblasts (CEFs) contain a low level of particle-associated reverse transcriptase (RT) activity, which is produced from the avian cell substrate. The RNAs present in the particles have sequence homology to viral DNAs belonging to the ancient endogenous avian virus (EAV) family or to the avian sarcoma-leukosis virus (ALV)-related subgroup E endogenous virus loci. Although no replication-competent retrovirus has been associated with the RT activity produced from CEFs, there have been some theoretical safety concerns regarding potential consequences of integration of EAV and ALV sequences in human DNA, which may result from nonproductive infection with replication-defective particles or infection with EAV and ALV pseudotypes bearing measles virus envelopes. To address these possibilities, we have analyzed EAV and ALV particles in a measles virus vaccine equivalent (MVVE) preparation, obtained from a U.S. manufacturer, for integration and for replication in human peripheral blood mononuclear cells (PBMCs). The results show the absence of EAV and ALV integrants in DNA prepared from MVVE-inoculated human cells by direct DNA PCR and Alu PCR assays and no propagation of retrovirus in 18-day cultures of MVVE-inoculated human PBMCs by a highly sensitive PCR-based RT assay. These results provide further confidence regarding the safety of chicken RT activity in live viral vaccines and support the continued use of chick-cell-derived vaccines in humans.